A Comparative Study of Social Media Data Using Weka Tool - kala, M. Saranya (International Journal of Computer Sciences and Engineering, 2025)
Social media is a growing trend in the world today. It is being utilized by students, parents, businesses and religious organizations. Nowadays mostly every human being becomes addicted to social media, i.e. Facebook, Twitter and WhatsApp. Usages of social media are increasing in trends. They can build a personal network of friends that is connected to an open worldwide community. Information is now shared freely between the two. These parties can communicate either publicly or via the more discrete personal message. In this paper contains Facebook, Twitter and WhatsApp dataset like status and profile photo. The goal here is to analyze the time execution, Execution process and frequency by implementing weka tool. Here analogize the three algorithms, namely K-means, Bayesion algorithm and apriori algorithm. In this research process, the three algorithms used to find the time execution, Execution process and frequency which are predicting time consumes